2016
DOI: 10.1080/15548627.2016.1243199
|View full text |Cite
|
Sign up to set email alerts
|

The 1:2 complex between RavZ and LC3 reveals a mechanism for deconjugation of LC3 on the phagophore membrane

Abstract: Hosts utilize macroautophagy/autophagy to clear invading bacteria; however, bacteria have also developed a specific mechanism to survive by manipulating the host cell autophagy mechanism. One pathogen, Legionella pneumophila, can hinder host cell autophagy by using the specific effector protein RavZ that cleaves phosphatidylethanolamine-conjugated LC3 on the phagophore membrane. However, the detailed molecular mechanisms associated with the function of RavZ have hitherto remained unclear. Here, we report on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 50 publications
0
43
0
Order By: Relevance
“…uncoupling GARARAP-L2 attached to PE on autophagosome membranes (Choy 337 et al, 2012, Kwon et al, 2017). We found that small amounts of RavZ could re-338 move GARABAP-L2 WT and S87/88D mutant from autophagosomes ( Figure 7C), 339…”
mentioning
confidence: 62%
“…uncoupling GARARAP-L2 attached to PE on autophagosome membranes (Choy 337 et al, 2012, Kwon et al, 2017). We found that small amounts of RavZ could re-338 move GARABAP-L2 WT and S87/88D mutant from autophagosomes ( Figure 7C), 339…”
mentioning
confidence: 62%
“…TBK1 phosphorylates PE-lipidated forms (-II) equally well as unlipidated (-I) LC3s (Fig 7B). RavZ is a bacterial effector protein from the intracellular pathogen Legionella pneumophila that interferes with autophagy by directly and irreversibly uncoupling GABARAP-L2 attached to PE on autophagosome membranes [33,34]. I II I GABARAP-L2-II GABARAP-L2-I&II LC3C-I LC3C-II LC3C-I&II II C I II I II I II I II I II 15 Finally, we also tested whether the phosphorylation of GABARAP-L2 has an impact on its de-lipidation from the phagophore by other proteases such as RavZ (Figs 7E and EV5A).…”
Section: Phospho-mimetic D C-terminal Lc3c and Gabarap-l2 Are Not Lipmentioning
confidence: 99%
“…A study combining chemical and structural approaches demonstrated that RavZ extracts LC3-PE from the membrane before deconjugation [68,69]. RavZ targets autophagosomal membrane via the C-terminal PI3P-binding domain and the α3 helix and recognizes the LC3 molecule on the membrane via its N-terminal LIR motif [69][70][71]. The RavZ α3 helix is involved in the extraction of the PE moiety and docking of the acyl chains into the lipid-binding site of RavZ that is related in structure to that of the phospholipid transfer protein Sec14 [69].…”
Section: Bacteria Inhibit Autophagosome Formationmentioning
confidence: 99%